Thermo-responsive injectable naringin-loaded hydrogel polymerised sodium alginate/bioglass delivery for articular cartilage - Xiang Li; Yang Lu; Yuxin Wang; Shengji Zhou; Liangping Li; Fengchao Zhao (Taylor & Francis Group, 2021)
In the human body, joint cartilage is of great importance. It has long been a big therapeutic problem to fix joint cartilage lesions as it appears due to different conditions. Recent stories have shown that the cartilage replacement process must delay the extracellular (ECM) cartilage deterioration and modulate the host's inflammation response. For the reconstruction of the articular cartilage, drug-loaded injectable hydrogels were developed. This hydrogel could retain the chondrocyte phenotype, but the host's inflammatory reaction could also be controlled. The bioglass (BG)/sodium alginate (SA) injectable hydrogels was combined with agarose (AG)/Naringin hydrogel in injectable thermal response for articular cartilage regeneration with a non-chargeable hydrogel that contains both Naringin and BG (Naringin-BG hydrogels). The Naringin-BG hydrogel has an adequate swelling ratio that encourages the fusion of tissue formed with host tissue and enables the gradual release of Naringin bioavailabilities enhanced in situ. The Naringin-BG hydrogel can upgrade the typical chondrocyte phenotype by upregulating aggrecan, SRY-box 9, and collagen type II alpha one chain. It may also stimulate the polarization of M2 macrophage, lower inflammations, and prevent ECM degradations through the decrease of the expressions of the indictable metalloproteinase-13 matrix, nitric oxide synthase, and metalloproteinase-1 matrix. The formed tissues were identical to normal tissues and firmly incorporated with the surrounding tissue after administering the Naringin-BG hydrogels into the rat model articular cartilage defects. Then the injectable Naringin-BG hydrogel increases the bioavailable content of Naringin and retains the chondrocyte phenotype.